Nanocompósitos para a liberação controlada de compostos triazínicos aplicados como defensivos agrícolas - Giroto, Amanda Soares (Universidade Federal de São Carlos, 2013)
This research proposed a preparation method for a nanocomposite, able to control the delivery of high quantities of an active compound, inserted on its matrix, in order to prospect an application for the controlled delivery of herbicides. To that, a nanocomposite system was prepared based on the exfoliation of a clay mineral in a continuous starch phase, loading around 50% weight of a model herbicide ametryne. The starch was loaded with 50 to 80% of montmorillonite, dispersed through the starch gelification at 90o C in water. The herbicide was added during the cooling process, at 70o C. The materials were characterized by X-ray diffraction and thermal analyses, where the intercalation of the biopolymer in the clay lamellar structure was observed. The herbicide release showed that the releasing behavior was governed by the starch amount in the nanocomposite, for short periods, and by the clay, in longer periods. It was observed also a synergic effect between the nanocomposite constituents, since the reference materials (produced with starch: ametryne or clay: ametryne) did not showed adequate release behaviors. However, this behavior was shown as governed by physical barriers for the ametryne diffusion, since nuclear magnetic resonance in solid state experiments showed that the starch: ametryne interactions were weak. On the other hand, the starch: clay interactions were shown by the same technique, supporting the synergic behavior of the release. Finally, the nanocomposite system improved the resistance to the UV light attack, reducing the herbicide volatilization under irradiation. This effect was evaluated by mass loss experiments after different irradiation times, compared to infrared spectroscopy measurements.
Nanocomposites for controlled delivery of triazinc compounds applied as agricultural pesticides
Keywords: Físico-química; Liberação controlada de pesticida; nanocompósitos; Argila; Amido; Fotodegradação; CIENCIAS EXATAS E DA TERRA::QUIMICA